2020
DOI: 10.1371/journal.pone.0229361
|View full text |Cite
|
Sign up to set email alerts
|

Can online support groups address psychological morbidity of cancer patients? An artificial intelligence based investigation of prostate cancer trajectories

Abstract: Background Online Cancer Support Groups (OCSG) are becoming an increasingly vital source of information, experiences and empowerment for patients with cancer. Despite significant contributions to physical, psychological and emotional wellbeing of patients, OCSG are yet to be formally recognised and used in multidisciplinary cancer support programs. This study highlights the opportunity of using Artificial Intelligence (AI) in OCSG to address psychological morbidity, with supporting empirical evidence from pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…All data sources are publicly available, and the entire data extraction process was anonymized. We applied a validated artificial intelligence framework, the Patient‐Reported Information Multidimensional Exploration (PRIME) framework [5, 6] on both data sets. The PRIME framework has been effectively used for the extraction, analysis and synthesis of patient‐reported information on physical and mental well‐being, such as symptoms, side effects, treatment decisions, real‐life experiences, mental health issues, and emotional burden of patients with cancer, cancer survivors, and caregivers [7].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…All data sources are publicly available, and the entire data extraction process was anonymized. We applied a validated artificial intelligence framework, the Patient‐Reported Information Multidimensional Exploration (PRIME) framework [5, 6] on both data sets. The PRIME framework has been effectively used for the extraction, analysis and synthesis of patient‐reported information on physical and mental well‐being, such as symptoms, side effects, treatment decisions, real‐life experiences, mental health issues, and emotional burden of patients with cancer, cancer survivors, and caregivers [7].…”
Section: Figurementioning
confidence: 99%
“…All data sources are publicly available, and the entire data extraction process was anonymized. We applied a validated artificial intelligence framework, the Patient-Reported Information Multidimensional Exploration (PRIME) framework [5,6]…”
mentioning
confidence: 99%
“…Men have been found to join PCSG at specific points in their disease process. Adikari, et al showed PCa patients join online support groups at four specific psychological phases: diagnosis, treatment, side-effects, and recurrence, with 67% of patients joining at the time of treatment initiation [25]. Carter, et al (2011) reported patients with advanced PCa are more likely to seek PCSGs and desire stage-specific information to address concerns about the diagnosis [26].…”
Section: Pcsg Participation and Benefitsmentioning
confidence: 99%
“…Given the volume and variety of content being shared on social media, online behaviors have been investigated as a proxy for offline human behaviors, with several studies reporting conclusive results and outcomes [16][17][18]. A massive number of social media conversations represents a cross-section of society that encompasses people's opinions across different demographic dimensions.…”
Section: Introduction Overviewmentioning
confidence: 99%
“…In this study, we focus on the application of artificial intelligence (AI) approaches that have been validated across several studies [18,27,38] to analyze human emotions. The algorithms are used to quantify emotion intensities, detect emotion state transitions, and identify profiles of impacted individuals based on the concerns they have expressed on social media to provide a holistic view of people's mental health.…”
Section: Introduction Overviewmentioning
confidence: 99%